Obtenção de estruturas porosas altamente bioativas via sinterização do Biosilicato® - Crovace, Murilo Camuri (2009)
In the present work, scaffolds were obtained through the controlled sintering of Biosilicate®. This material possesses good mechanical properties and its bioactivity level is comparable to that of bioglasses, making it an interesting candidate for use as a scaffold to stimulate bone tissue regeneration. Previous studies have found that a secondary crystalline phase is formed when Biosilicate® is heat-treated at high temperatures (T > 700°C). The in vitro bioactivity tests revealed that the presence of the secondary phase is not harmful, but instead enhances the bioactivity of Biosilicate® to a level comparable to that of Bioglass - 45S5. Two different techniques were used in the synthesis of scaffolds: (1) the addition of porogen agents, and (2) the replication method. Five porogen agents were tested and compared: naphthalene, cassava starch, corn starch, polyethylene beads and carbon black. The first technique yielded scaffolds with a total porosity of 67 to 87% in a highly interconnected porous structure. The best result was achieved with carbon black, which resulted in an average pore size of 230 μm and a total porosity of 87%, making it the most promising porogen agent for application as a scaffold. The replication technique led to the formation of scaffolds with a total porosity of 96% and open cells in the range of 435 945 μm, with an average cell size of 650 μm.